(3QSGdI aj GdebGOjQ GdeTJQcI hGdeJHGjfIs - (3CHh YHO Gddg GdMSf Hf eMeO Hf MedI Hf GdHZOGOj, GHf GdHZOGOjs
(3ChdgG (B:s
(3EYde CQTOc Gddg Gfg dGSHjd Edi eYQaI GdETJQGc hGdJHGjf ai GdGbOGQ ZdG HYO Gdhbha Ydi aQb eG Hjf GdYOO hGdeYOhO heG jNU cd hGMO efgeG HPGJg s
(3BNQgG (B:s
(3aEf GdGYOGO JbY Ydjg HebOGQ eG jYOg CLRGAg GdeTJQcI Hjfg hHjfgG hGdMeO ddg hMOg s
(3HgG QShe hCTcGds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdQjGVjGJs